Applications and Properties of Magnetic Nanoparticles - Arosio, Paolo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue aimed to cover the new developments in the synthesis and characterization of magnetic nanoconstructs ranging from conventional metal oxide nanoparticles to novel molecule-based or hybrid multifunctional nano-objects. At the same time, the focus was on the potential of these novel magnetic nanoconstructs in several possible applications, e.g. sensing, energy storage, and nanomedicine.